2004
DOI: 10.1137/s0036144503439190
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Public-Key Cryptosystems

Abstract: We give an overview of the most important public-key cryptosystems and discuss the difficult task of evaluating the merit of such systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 104 publications
0
29
0
Order By: Relevance
“…At the heart of this concept is the idea of using a one-way function for encryption (see the survey paper of Koblitz and Menezes [73]). …”
Section: What Is Public-key Cryptography?mentioning
confidence: 99%
See 1 more Smart Citation
“…At the heart of this concept is the idea of using a one-way function for encryption (see the survey paper of Koblitz and Menezes [73]). …”
Section: What Is Public-key Cryptography?mentioning
confidence: 99%
“…The idea of public-key cryptography in general is to make it possible for two parties to agree on a shared secret key, which they can use to transfer data in a secure way (see [73]). There are several known public-key cryptosystems which are based on the discrete logarithm problem, which is the problem of finding x in the equation g x = h where g, h are given, and on the factorization problem, which is the problem of factoring a number to its prime factors: DiffieHellman [38] and RSA [106].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is shown that cryptosystem proved secure in the traditional model may not resist the side-channel attacks [6] which can recover a fraction of the secret key to the adversary. To protect against above realistic attacks in the provable security approach, one can model them using abstract notions of computation which leads to many studies made in leakage-resilient cryptography.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm is known as DSA, for Digital Signature Algorithm [13,12,10]. It is an efficient variant of the ElGamal digital signature scheme [4] intended for use in electronic mail, electronic funds transfer, electronic data interchange, software distribution, data storage, and other applications which require data integrity assurance and data authentication.…”
Section: Introductionmentioning
confidence: 99%
“…It is an efficient variant of the ElGamal digital signature scheme [4] intended for use in electronic mail, electronic funds transfer, electronic data interchange, software distribution, data storage, and other applications which require data integrity assurance and data authentication. In 1998, an elliptic curve analogue called Elliptic Curve Digital Signature Algorithm (ECDSA) was proposed and standardized [5,9,10].…”
Section: Introductionmentioning
confidence: 99%